Distinction of Fly Artifacts from Bloodstains in Crime Scenes: A Brief Literature Review - Soumeek Chowdhuri; Somasish Ghosal; Saurabh Chattopadhyay; Achintya Biswas; Abhishek Das; Subhankar K. Sarkar (Arab Journal of Forensic Sciences & Forensic Medicine, 2022)
Insect artifacts produced by necrophagous adult flies over a variety of depositional surfaces are problematic in crime scene investigations. Assessment of bloodstains through morphological features combined with contextual and presumptive chemical analysis, as traditional practices, are often inconclusive. Absorbance of bloodstains and substantial wicking on fabrics due to underlying texture and repeated stitch loops in the fabric makes the diagnosis even more difficult than stain morphology.